2005
DOI: 10.1111/j.1600-0579.2004.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well‐being and perceptions of stress amongst Japanese dental students

Abstract: The purpose of this study was to investigate the relationship between Psychological General Well Being (PGWB) and perceived sources of stress amongst dental students in Japan. Second to sixth year dental students of Tokyo Medical and Dental University were invited to participate in the questionnaire survey. The questionnaire collected information on demographic and social background, lifestyle behaviours, the PGWB index and the Dental Environment Stress (DES) questionnaire. A total of 320 students (56% male) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
132
6
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(184 citation statements)
references
References 28 publications
(47 reference statements)
26
132
6
10
Order By: Relevance
“…In a previous study, DES was divided theoretically into five domains with a general alpha of 0.95 [23]. Br-DES general alpha was consistent to previous reports [7,11,19]; alpha values from 0.70 to 0.95 are considered acceptable but a very high value may indicate redundancy between items [24]. But, the study did not test discriminant validity and its cross-sectional design did not allow for testing the stability and responsiveness of the instrument, i.e., its ability to reproduce the same results in successive applications, and to detect changes over time.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In a previous study, DES was divided theoretically into five domains with a general alpha of 0.95 [23]. Br-DES general alpha was consistent to previous reports [7,11,19]; alpha values from 0.70 to 0.95 are considered acceptable but a very high value may indicate redundancy between items [24]. But, the study did not test discriminant validity and its cross-sectional design did not allow for testing the stability and responsiveness of the instrument, i.e., its ability to reproduce the same results in successive applications, and to detect changes over time.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, although DES has been used in many countries, among different cultures, few studies have demonstrated its properties or methods of cultural adaptation prior to describe the perceived stressors [6,7,10,11,19]. Satisfactory results of this study, both in regard to semantic equivalence and actual measurements, suggest that the cultural adaptation process of the Brazilian/Portuguese version of DES was adequate.…”
Section: Discussionmentioning
confidence: 55%
“…In addition they had spent a month of immersion in an educational environment, acquiring in this way an idea or knowledge about what will be his university career. Class size, leisure time, assessment procedures, peer and professor relationships, ethical climate, extracurricular opportunities, beliefs, attitudes and sociocultural background significantly influence the way students perceive and experience their education [11][12][13]. The Garbee's Dental Environment Stressors modified previously by some authors [13,14] has been widely used in research studies in Europe, Japan and Australia [2,15,[16][17][18][19].…”
Section: Data Collectionmentioning
confidence: 99%
“…Faculty of Tokyo medical & dental university (TMDU) 24 planed to launch a view on curriculum including problem based learning & early exposure systems, along with providing greater flexibility for students to develop professional attitude. The reconsideration of the existing educational system towards a more students centured orientation could facilitate collaboration learning and interpersonal support amongst students, which may have a productive effect against difficulties faced whilst in dental institution.…”
Section: Disscussionmentioning
confidence: 99%